A Peningkatan Kemampuan Pemahaman Konsep Matematis Siswa Sekolah Dasar Melalui Model Pembelajaran Problem Based Learning: Peningkatan Kemampuan Pemahaman Konsep Matematis Siswa Sekolah Dasar Melalui Model Pembelajaran Problem Based Learning - Rahmat Yudi Guntara; Zulfah; Syahrial; Yanti Yandri Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the mathematical conceptual understanding of students through the implementation of the Problem-Based Learning model in Grade V students of MI AL-Fitrah. The problem faced was the low level of students’ conceptual understanding in mathematics, as indicated by the large number of students struggling to solve math-related problems, decreased self-confidence, reliance on formulas without understanding, declining learning outcomes, and imbalance in the learning process. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were 13 fifth-grade students. Data were collected through observation, tests, and documentation. The results showed an improvement in students’ mathematical conceptual understanding after the implementation of the Problem-Based Learning model. In the pre-cycle, only 38% of students achieved mastery. After the implementation of Cycles I and II, the percentage of mastery increased significantly. Based on these results, it can be concluded that the Problem-Based Learning model is effective in improving students’ understanding of mathematical concepts. This model provides opportunities for students to learn actively and independently in discovering and understanding mathematical concepts.